Impact of Implementation of ISO 14001 Environmental Management Systems on Environmental Performance: A Case Study - Ho, Lee Lee; Law, Puong Ling (IJERST, 2015)
The Environmental Management System (EMS) structure recognizes that both environmental and economic performances are directly linked with each other. The primarily objective of implementing an EMS is to improve an organization’s environmental performance continuously. Benefits of successful implementation of an EMS would include cost reduction in pollution prevention activities, compliance with legislation requirements, and a better organizational image internationally and locally. This study looks into one of the most common EMS frameworks, namely ISO 14001 EMS. This study also investigates the relation of EMS implementation to environmental performance improvement. Empirical findings of a recent study on the above in a manufacturing facility which implemented ISO 14001 EMS are presented. This company had been implemented ISO 14001 EMS since 2004 and certified in early 2005. From January 2004 until August 2010, a total of thirteen Environmental Management Programs (EMP) were implemented. Out of the thirteen EMP implemented, five EMP were for legal compliances; four EMP were for environmental operational control and the other four were for cost reduction through water and chemical conservation. In August 2010, eleven EMP had already achieved the environmental performance indicators set, compliance to legal requirements and better environmental operational control that resulted in better environmental performance; water and chemical conservation that led to cost reductions. The other two EMP were still on-going while some new EMP were planned too.